Cerebrospinal fluid cholinergic biomarkers are associated with postoperative delirium in elderly patients undergoing Total hip/knee replacement: a prospective cohort study - Xu Lin; Jiaming Tang; Chen Liu; Xiaoxuan Li; Xipeng Cao; Bin Wang; Rui Dong; Wei Xu; Xinjuan Yu; Mingshan Wang; Yanlin Bi (BMC Anesthesiology, 2020)
Abstract Background Postoperative delirium (POD) is a frequent complication after surgery and its occurrence is associated with poor outcomes. The neuropathology of this complication is unclear, but it is important to evaluate relevant biomarkers for postoperative status. The purpose of this study is to explore the relationship between expression levels of cholinergic biomarkers in cerebrospinal fluid (CSF) and the occurrence and development of POD in elderly patients. Methods Four hundred and ninety-two elderly patients aged 65 years old or older with elective total hip/knee replacement received combined spinal-epidural anesthesia. Preoperative baseline cognitive function was assessed using the Mini-Mental State Examination (MMSE) before surgery. Each patient was interviewed in post-anesthesia care unit (PACU) and on the first, second, third and seventh (or before discharge) postoperative days. POD was diagnosed using the Confusion Assessment Method (CAM), and POD severity was measured using the Memorial Delirium Assessment Scale (MDAS). Preoperative CSF and plasma choline acetyltransferase (ChAT), acetylcholinesterase (AChE), butyrylcholinesterase (BuChE), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) levels were determined by ELISA. The levels of ChAT, AChE and BuChE activities were determined by spectrophotometry. Results POD was detected in 11.4% (51/447) of the patients. AChE, BuChE, ChAT, TNF-α and IL-6 concentrations in CSF and plasma have higher consistency. In preoperative CSF and preoperative and postoperative plasma, down-regulation of the concentration and activity of AChE and BuChE as well as up-regulation of the concentration and activity of ChAT and the concentrations of IL-6 and TNF-α were observed in patients who developed POD, and the decrease in BuChE was the most obvious. Logistic analysis showed the activities of ChAT, AChE and BuChE in CSF were still related to POD after adjusting for related factors such as sex, age, years of education, height, weight, body mass index (BMI), and American Society of Anesthesiologists (ASA) class. Receiver Operating Characteristic (ROC) curve analysis was conducted to determine the Area Under Curve (AUC) of AChE, BuChE and ChAT activity in CSF was 0.679 (P < 0.01), 0.940 (P < 0.01) and 0.819 (P < 0.01) respectively and found that BuChE activity had the most accurate diagnostic value. Conclusion The changes in preoperative activity of AChE, BuChE and ChAT in CSF were associated with the development of POD in elderly patients, and BuChE activity had the greatest diagnostic value, which may be related to central cholinergic degradation. These cholinergic biomarkers might participate in the neuropathology of POD, pending further investigations. Trial registration This study was registered at Chictr.org.cn (NO. ChiCTR1900023729 ) June 9th, 2019. (Retrospectively registered).